Water arsenic removal for human consumption using Mg/Fe layered double hydroxide - Ceseña Quiñonez, Jose Ignacio; Ramos Ramírez, Esthela; Serafín Muñoz, Alma Hortensia; Moreno Palmerin, Joel; Zanor, Gabriela Ana; Gutiérrez Ortega, Norma Leticia (Acta Universitaria, 2019)
Water contamination by arsenic is a serious public health problem worldwide. The use of mesoporous hydrotalcite compounds is an efficient and practical option for the adsorption of arsenic, due to its high removal rate and low cost. A Mg/Fe layered double hydroxide was synthesized by the coprecipitation method to eliminate arsenic in contaminated water. This solid was treated at 100 °C and 350 °C. The solid was characterized by XRD and DSC-TGA. Arsenic removal tests were carried out by contact at the equilibrium in the Bach system with synthetic arsenic solutions and natural spring samples. The thermally treated solid at 350 °C showed the best arsenic removal capacity, with an adsorption capacity of 447.7 mg of arsenic per g of adsorbent in a time of 180 min. This capacity is attributed to the structural modification by the heat treatment.